Pengolahan Sampah Berbasis Masyarakat Dalam Mendukung Kampung Iklim Kelurahan Tambakrejo Semarang - Sidiq, Wahid Akhsin Budi Nur; Gustaman, Fulia Aji; Hermanto, Fredy (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2025)
The phenomenon of climate change has a very pronounced impact on Semarang City, especially in Tambakrejo Village with increased risk of disasters such as flooding and tidal floods. Various efforts in reducing the risk of climate change have been carried out through the Climate Village Program (ProKlim) with the aim of increasing community participation in waste management. Currently, inorganic waste management has been carried out by the Berkah Jaya Waste Bank but it is not optimal, while for organic waste management it still does not exist. The purpose of the service activity is to make household waste management more organized so that it supports the Climate Village Program. Activity methods through counseling, training, technical guidance, field practice, equipment facilitation and program development. The results of activities in the form of increasing partners' understanding and skills in waste management with several activities including socialization of household-based waste management, increasing community capacity in processing organic waste, facilitating facilities and infrastructure for organizing waste processing sites and developing waste bank savings programs. Another result is an increase in sales of inorganic waste from the Berkah Jaya Waste Bank, where from waste management it can buy waste from residents amounting to Rp.2,749,350, - with sales of Rp.3,376,200, - during February - June. The conclusion of this activity is that there is an increase in organic and inorganic waste management in target partners.